CD44 isoforms containing exon V3 are responsible for the presentation of heparin-binding growth factor. - Bennett, K; Jackson, D; Simon, J; Tanczos, E; Peach, R; Modrell, B; Stamenkovic, I; Plowman, G; Aruffo, A (1995)
Glycosaminoglycan-modified isoforms of CD44 have been implicated in growth factor presentation at sites of inflammation. In the present study we show that COS cell transfectants expressing CD44 isoforms containing the alternatively spliced exon V3 are modified with heparan sulfate (HS). Binding studies with three HS-binding growth factors, basic-fibroblast growth factor (b-FGF), heparin binding-epidermal growth factor (HB-EGF), and amphiregulin, showed that the HS-modified CD44 isoforms are able to bind to b-FGF and HB-EGF, but not AR. b-FGF and HB-EGF binding to HS-modified CD44 was eliminated by pretreating the protein with heparitinase or by blocking with free heparin. HS-modified CD44 immunoprecipitated from keratinocytes, which express a CD44 isoform containing V3, also bound to b-FGF. We examined whether HS-modified CD44 isoforms were expressed by activated endothelial cells where they might present HS-binding growth factors to leukocytes during an inflammatory response. PCR and antibody-binding studies showed that activated cultured endothelial cells only express the CD44H isoform which does not contain any of the variably spliced exons including V3. Immunohistological studies with antibodies directed to CD44 extracellular domains encoded by the variably spliced exons showed that vascular endothelial cells in inflamed skin tissue sections do not express CD44 spliced variants. Keratinocytes, monocytes, and dendritic cells in the same specimens were found to express variably spliced CD44. 35SO4(-2)-labeling experiments demonstrated that activated cultured endothelial cells do not express detectable levels of chondroitin sulfate or HS-modified CD44. Our results suggest that one of the functions of CD44 isoforms expressing V3 is to bind and present a subset of HS-binding proteins. Furthermore, it is probable that HS-modified CD44 is involved in the presentation of HS-binding proteins by keratinocytes in inflamed skin. However, our data suggests that CD44 is not likely to be the proteoglycan principally involved in presenting HS-binding growth factors to leukocytes on the vascular cell wall.